2005
DOI: 10.1128/aem.71.9.5290-5296.2005
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Activity and Stability of GL-7-ACA Acylase CA130 by Site-Directed Mutagenesis

Abstract: In the present study, glutaryl-7-amino cephalosporanic acid acylase from Pseudomonas sp. strain 130 (CA130) was mutated to improve its enzymatic activity and stability. Based on the crystal structure of CA130, two series of amino acid residues, one from those directly involved in catalytic function and another from those putatively involved in surface charge, were selected as targets for site-directed mutagenesis. In the first series of experiments, several key residues in the substrate-binding pocket were sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Previously it was shown that introduction of the double Kβ198A/Qβ50N mutation in Pseudomonas 130 GLA increases enzyme stability and activity (Zhang et al, 2005). We have introduced orthologous mutation in our BrdGLA/ChBD fusion protein and have studied properties of the mutant enzyme.…”
Section: Site-directedmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously it was shown that introduction of the double Kβ198A/Qβ50N mutation in Pseudomonas 130 GLA increases enzyme stability and activity (Zhang et al, 2005). We have introduced orthologous mutation in our BrdGLA/ChBD fusion protein and have studied properties of the mutant enzyme.…”
Section: Site-directedmentioning
confidence: 99%
“…The stability of the double-mutant at pH optimal for the wild type protein also did not increase: after 70 hours of incubation at 35°C and pH 7.0 the residual activity of the mutant protein was just 15% lower than the activity of the wild-type protein. Taking into account the reported influence of the Qβ50N mutation on pH-optimum of mutant enzyme and its stability at alkaline conditions (Zhang et al, 2005) we have studied the rate of thermal inactivation of the double mutant at pH 10.0. Results in comparison with previous experiment are shown on Fig.…”
Section: Site-directedmentioning
confidence: 99%
See 1 more Smart Citation
“…The semi-synthetic cephalosporins became the popular antibiotics due to their excellent characteristics such as broad-spectrum, low toxicity, and resistance to the β-lactamase and it made tremendous contribution to fight with bacterial infection (Ren, 2013). The chemical conversion of cephalosporin C to 7-aminocephalosporanic acid (7-ACA 2 ) is usually accomplished by using chemicals which creates serious disadvantages such as requirement of multistep and complex process, low quantity and quality of product (Zhang et al, 2005;Kim et al, 2000;Lein, 1989;Nigam et al, 2005). Thereby the chemical method has been replaced by an enzymatic method for preparing 7-ACA which can be regarded as an environmentally safe method.…”
Section: Introductionmentioning
confidence: 99%
“…When improving the properties of the support is no longer possible, to further increase the strength of protein adsorption we propose to remodel the enzyme surface by site-directed mutagenesis in order to improve its complementarity with the ionic exchanger, increasing the number of ionic groups in the enzyme surface capable of interacting with the support (that is, exposed to the medium). Therefore, we propose to carry out genetic modifications of the proteins, not to directly improve the enzyme properties (18,28,29,53) but to produce an enzyme with better characteristics to facilitate its immobilization by a very simple technique as its adsorption on anionic exchangers.…”
mentioning
confidence: 99%